Digitalization of the Qur’an and Interpretation: Contribution of Social Media to the Study of Qur’an Interpretation - Sutrisno, Febby Intansari Nuraini (Maliki Interdisciplinary Journal, 2025)
The advancement of science and technology (IPTEK) has brought significant changes in various aspects of life, including religion. Social media as part of new media has changed the way Muslims interact with the Qur’an, including in understanding and studying it. This study aims to analyze how social media influences the interpretation of the Qur’an, focusing on the case study of Nadirsyah Hosen and the phenomenon of dissemination of religious content on social media platforms. This study uses a qualitative method with a case study approach. This study also found that social media allows for broader dialogue and discussion regarding the interpretation of the Qur’an, but also opens up the potential for diverse and even controversial interpretations. In addition, this study highlights the importance of verifying sources and references in the interpretation of the Qur’an on social media to avoid the spread of inaccurate or misleading information.